Professional communication competence in English for occupational purposes (EOP) courses: A systematic literature review and proposal of a framework - Maisarah Ahmad Kamil; Ahmad Mazli Muhammad (Journal of Teaching and Learning for Graduate Employability, 2021)
This paper reports a systematic literature review that was conducted to explore the areas of research pertaining to English language workplace communication needs in order to design courses in English for Occupational Purposes (EOP) that can better meet the demands of the industry. Articles from Scopus, ScienceDirect and Emerald Insight were extracted following the five-step method of conducting a systematic literature review. In total, 133 articles were analysed. From the analysis, it was found that most studies focused on examining the needs of the learners, or the needs of the industry; very few studies triangulated the findings between different stakeholders to obtain a better picture of the needs, wants, and gaps between the target situation and the present situation. Additionally, most studies focused on language tasks required and did not pay due emphasis on the competencies required to perform the tasks well. Thus, the outcome of this review is a proposed theoretical model to develop professional communication competence among new graduates that is intended to be used in a future study to address the gaps found in this review. Practically, the review also sheds light on gaps that exist in current research that can be addressed in future research, especially for higher education institutions (HEIs) that are working to design and develop courses in EOP to improve English language communication skills for employability.